Concise Encyclopedia of Biomedical Polymers and Polymeric Biomaterials - Mishra, Munmaya K. (CRC Press, 2017)
"The Concise Encyclopedia of Biomedical Polymers and Polymeric Biomaterials presents new and selected content from the 11-volume Biomedical Polymers and Polymeric Biomaterials Encyclopedia. The carefully culled content includes groundbreaking work from the earlier published work as well as exclusive online material added since its publication in print. A diverse and global team of renowned scientists provide cutting edge information concerning polymers and polymeric biomaterials. Acknowledging the evolving nature of the field, the encyclopedia also features newly added content in areas such as tissue engineering, tissue repair and reconstruction, and biomimetic materials."--Provided by publisher.